Association of Modality with Mortality among Canadian Aboriginals - Sood, Manish M. (American Society of Nephrology, 2012)
BACKGROUND AND OBJECTIVES: Previous studies have shown that Aboriginals and Caucasians experience similar outcome on dialysis in Canada. Using the Canadian Organ Replacement Registry, this study examined whether dialysis modality (peritoneal or hemodialysis) impacted mortality in Aboriginal patients. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This study identified 31,576 adult patients (hemodialysis: Aboriginal=1839, Caucasian=21,430; peritoneal dialysis: Aboriginal=554, Caucasian=6769) who initiated dialysis between January of 2000 and December of 2009. Aboriginal status was identified by self-report. Dialysis modality was determined 90 days after dialysis initiation. Multivariate Cox proportional hazards and competing risk models were constructed to determine the association between race and mortality by dialysis modality. RESULTS: During the study period, 939 (51.1%) Aboriginals and 12,798 (53.3%) Caucasians initiating hemodialysis died, whereas 166 (30.0%) and 2037 (30.1%), respectively, initiating peritoneal dialysis died. Compared with Caucasians, Aboriginals on hemodialysis had a comparable risk of mortality (adjusted hazards ratio=1.04, 95% confidence interval=0.96–1.11, P=0.37). However, on peritoneal dialysis, Aboriginals experienced a higher risk of mortality (adjusted hazards ratio=1.36, 95% confidence interval=1.13–1.62, P=0.001) and technique failure (adjusted hazards ratio=1.29, 95% confidence interval=1.03–1.60, P=0.03) than Caucasians. The risk of technique failure varied by patient age, with younger Aboriginals (<50 years old) more likely to develop technique failure than Caucasians (adjusted hazards ratio=1.76, 95% confidence interval=1.23–2.52, P=0.002). CONCLUSIONS: Aboriginals on peritoneal dialysis experience higher mortality and technique failure relative to Caucasians. Reasons for this race disparity in peritoneal dialysis outcomes are unclear.